Measurement of the top quark mass in the dileptonic t(t)over-bar decay channel using the mass observables M-bl, M-T2, and M-blv in pp collisions at root=8 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2017)
A measurement of the top quark mass (M-t) in the dileptonic t (t) over bar decay channel is performed using data from proton-proton collisions at a center-of-mass energy of 8 TeV. The data was recorded by the CMS experiment at the LHC and corresponds to an integrated luminosity of 19.7 +/- 0.5 fb(-1). Events are selected with two oppositely charged leptons (l = e, mu) and two jets identified as originating from b quarks. The analysis is based on three kinematic observables whose distributions are sensitive to the value of Mt. An invariant mass observable, M-bl, and a stransverse mass observable, M-T2, are employed in a simultaneous fit to determine the value of M-t and an overall jet energy scale factor (JSF). A complementary approach is used to construct an invariant mass observable, M-blv, that is combined with M-T2 to measure M-t. The shapes of the observables, along with their evolutions in M-t and JSF, are modeled by a nonparametric Gaussian process regression technique. The sensitivity of the observables to the value of M-t is investigated using a Fisher information density method. The top quark mass is measured to be 172.22 +/- 0.18(stat)(-0.93)(+0.89) (syst) GeV.
Keywords: TEVATRON